Synthesis, characterization and comparative electrochemistry of beta and alpha tetra-[4-oxy-3-methoxybenzoic acid]-substituted Zn(II), Co(II) and Cu(II) phthalocyanines - ÖZKAYA, ALİ RIZA (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this study, novel beta and alpha tetra-[4-oxy-3-methoxybenzoic acid]-substituted Co(II), Zn(II) and Cu(II) phthalocyanines were prepared by the cyclotetramerization of the new phthalonitriles (1)/(2) and the corresponding divalent metal salts. The compounds were characterized by spectral data (IR, UV-Vis, H-1 NMR and mass spectroscopies) as well as elemental analysis. These metallophthalocyanines showed excellent solubility in most organic solvents. The reduction and oxidation behaviour of the alpha-and beta-substituted complexes were established by voltammetry and in situ spectroelectrochemistry. The complexes were observed to display metal- and/or phthalocyanine ring-based redox processes. The redox and aggregation behaviours of the phthalocyanine complexes were found to be affected considerably by the nature of the substitution. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; 4-Hydroxy-3-methoxybenzoic acid; Electrochemistry; Voltammetry; Spectroelectrochemistry; SUBSTITUTED METAL-FREE; COBALT PHTHALOCYANINE; SPECTROELECTROCHEMICAL INVESTIGATIONS; ELECTRICAL-PROPERTIES; ZINC PHTHALOCYANINES; PHOTODYNAMIC THERAPY; COMPLEXES; OXIDATION; METALLOPHTHALOCYANINES; REDUCTION